Treatment of synthetic wastewater by using submerged attached growth media in continuous activated sludge reactor system - Al-Dhawi, B.N.S. (Sustainable Building Research Center, 2022)
In biological wastewater treatment, an attached-growth system utilizes microorganisms that are attached to the fixed media to remove organic matter, nutrients, and other constituents in wastewater. The most affordable among all technology is biological wastewater treatment for the treatment of synthetic domestic wastewater. The conventional wastewater treatment plants continue to struggle to meet Malaysian discharge limits. Stringent regulation enforced by governing authoritiesâ making it obligatory to comply with discharge guidelines to fulfil organic contamination levels. To assist the system in meeting these limits, it is recommended that a submerged attached growth can be incorporated into the conventional treatment system. Two parallel continuous flow-activated sludge systems treating synthetic wastewater were used. In Reactor A, POC was used as the submerged attached growth media while Reactor B was used as a control reactor. The bioreactor has a volume of 10 L. The studies were carried out at various influent flow rates of 5, 10, 15, 20, 25, and 30 L/d, and constant organic load rate OLR. The influent and effluent were sampled every two days. Parameters COD, MLSS, and MLVSS were monitored. Generally, COD was highly removed. The average removal of COD reached 96 for reactor A while 88 for reactor B. Overall, the system demonstrated higher treatment efficiency of COD removal. Kinetic models, Monod was applied. Monod was ideal for explaining the experimental data in terms of microbial growth parameters. Ks was obtained as 223.97 and 370 g/m3 for reactor A and B respectively, while (Âµmax) 0.25 and 0.16 per day with a correlation coefficient (R2) of 0.9435 and 0.8799, for reactor A and B, respectively. Therefore, the models can be used in designing a submerged attach growth system and consequently predict the bioreactor behaviour. Â© International Journal of Sustainable Building Technology and Urban Development.